The International Monetary Fund in the global economy : banks, bo nds, and bailouts - Copelovitch, Mark S., 1975- (Cambridge ; New York : Cambridge University Press, 2010)
"The explosive growth and increasing complexity of global financial markets are defining characteristics of the contemporary world economy. Unfortunately, financial globalization has been accompanied by a marke d increase in the frequency and severity of financial crises. The Inter national Monetary Fund (IMF) has taken a central role in managing these crises through its loans to developing countries. Despite extensive an alysis and criticism of the IMF in recent years, key questions remain u nanswered. Why does the Fund treat some countries more generously than others? To what extent is IMF lending driven by political factors rathe r than economic concerns? In whose interests does the IMF act? In this book, Mark Copelovitch offers novel answers to these questions. Combini ng statistical analysis with detailed case studies, he demonstrates how the politics and policies of the IMF have evolved over the last three decades in response to fundamental changes in the composition of intern ational capital flows"--Provided by publisher.
The International Monetary Fund in the global economy -- Global fina nce and the politics of IMF lending: theory --- Global finance and the politics of IMF lending: evidence -- Global finance and IMF lending to Mexico, 1983-1995 -- Global finance and IMF lending to Korea, 1983-199 7.
Includes bibliographical references (p. 350-362) and index.
Keywords: International Monetary Fund; International economic relations; Globalization; Policy sciences; Bailouts (Government policy)